Content Analysis of Environmental Care Messages in TikTok Bumijo Content - Dhea Anggraeni, Afifah Arsi; Wardhana, Ardiyanto (Jogjakarta Communication Conference (JCC), 2024)
Conservation of the environment impacts the survival of the human species. Pleasant environmental circumstances might produce positive consequences that can be managed. However, a substantial amount of the population remains unconcerned about the need to protect the environment. Environment-related problems might develop from the consequences of global warming, air pollution, and garbage management. Indonesia is heavily impacted by environmental issues, with an annual waste production of 13 million tons and 4 million tons of unmanaged waste each year (SIPSN, 2023). This quantity of waste comes in large part from the consumption of plastic products and non-eco-friendly items that make them harder to dispose of. Bumijo.id is a TikTok account that supports and stands for eco-friendly projects. Bumijo.id uses social media platforms to motivate consumers to engage in ecological preservation efforts, such as enrolling in activities that focus on protecting the environment and embracing ecologically sustainable products to minimize trash generation. This study examines the substance of environmental care messages on the Bumijo.id TikTok account. This study uses a qualitative research approach, specifically adopting content analysis methodologies, to examine the messages within the contents published by Bumijo.id. The research specifically focuses on content that promotes environmental sustainability. This research uses message study theory as analysis material. Therefore, this study offers a valuable understanding of the application of social media, which can effectively contribute to the promotion of environmental conservation.